Influence of Costimulatory Molecules on Immune Response to Leishmania major by Human Cells In Vitro - Brodskyn, Claudia I. (American Society for Microbiology, 2001)
The importance of CD40, CD80, and CD86 costimulatory molecules in anti-Leishmania immune responses has been established in murine models. A role for these costimulatory molecules in human anti-Leishmania immune responses was investigated in this study. Autologous macrophages and peripheral blood leukocytes (PBL) were prepared from peripheral blood mononuclear cells of Leishmania-naive donors and cultured with or without Leishmania major in various combinations. After 7 days of culture, high levels of CD40 and CD86 were expressed on macrophages in the presence or absence of L. major. When macrophages were cultured for an additional 7 days with PBL, expression of all three costimulatory molecules was detected. When L. major was present in these cultures, the expression of CD80, and to a lesser extent CD40, on macrophages was enhanced. Blockade of CD80, CD86, or both molecules (in the order of greatest effect) in cultures containing macrophages, PBL, and L. major significantly inhibited the production of gamma interferon, interleukin-5 (IL-5), and IL-12. Blockade of CD40-CD154 interactions also significantly inhibited production of these cytokines in response to L. major. Production of IL-10 was unaltered by the blockade of these costimulatory molecules. Thus, these data suggest that CD40, CD80, and CD86 expression and regulation may significantly impact anti-Leishmania immune responses in humans.